2011
DOI: 10.4315/0362-028x.jfp-08-403
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Listeria monocytogenes and Escherichia coli O157:H7 Biofilms by Micelle-Encapsulated Eugenol and Carvacrol

Abstract: Carvacrol and eugenol were encapsulated in micellar nonionic surfactant solutions to increase active component concentrations in the aqueous phase and used to treat two strains of Listeria monocytogenes (Scott A and 101) and two strains of Escherichia coli O157:H7 (4388 and 43895) grown as biofilms in a Centers for Disease Control and Prevention reactor. L. monocytogenes biofilms were grown in two different growth media, 1:20 TSB and Modified Welshimer's broth (MWB), while E. coli O157:H7 was grown in M9. In g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
43
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(51 citation statements)
references
References 44 publications
2
43
0
2
Order By: Relevance
“…In order to improve the distribution of EOs/EOCs in food matrices and reduce interference by food components, various delivery systems, such as emulsions (9,10) and biopolymer capsules (6,(11)(12)(13), have been studied to enhance the antimicrobial activity and reduce the usage level. Commonly, the efficacy of delivery systems is compared to the same concentrations of free (unencapsulated) EOs/EOCs.…”
mentioning
confidence: 99%
“…In order to improve the distribution of EOs/EOCs in food matrices and reduce interference by food components, various delivery systems, such as emulsions (9,10) and biopolymer capsules (6,(11)(12)(13), have been studied to enhance the antimicrobial activity and reduce the usage level. Commonly, the efficacy of delivery systems is compared to the same concentrations of free (unencapsulated) EOs/EOCs.…”
mentioning
confidence: 99%
“…The concentration of 78 µg ml -1 produced a greater reduction in the number of bacterial cells that adhered to the microplate. The authors used SEM and found that the amount of biofilm was reduced in the presence of 39 µg ml -1 carvacrol and was almost absent at 78 µg ml Interesting findings were also reported by PerezConesa et al [7] who assessed the effects of encapsulated carvacrol on the inactivation of L. monocytogenes and E. coli O157:H7 biofilms on stainless steel. The morphological evaluation of biofilm revealed an increasing number of dead cells when the biofilms were treated with sufficiently high concentrations of carvacrol and a reduction of bacterial counts.…”
Section: Discussionmentioning
confidence: 64%
“…To enhance shelf life and avoid the degradation of EO in supplemented feed, the encapsulation of EOs could be a plausible means of delivering active EOs into the fish gut, as this would reduce interactions with the food matrix and possibly reduce any toxic effects. This approach has recently been evaluated, and the application of this method to aquaculture is highly promising Piva et al, 2007;Pérez-Conesa et al, 2011;van Vuuren et al, 2010;Donsi et al, 2011).…”
Section: Essential Oils: Antibacterial Properties and Potential Applimentioning
confidence: 99%